Lipid-coated ZnO nanoparticles as lymphatic-targeted drug carriers: study on cell-specific toxicity in vitro and lymphatic targeting in vivo. Issue 26 (8th June 2015) - Zeng, Ke; Li, Jin; Zhang, Zhaoguo; Yan, Mina; Liao, Yunhui; Zhang, Xuefei; Zhao, Chunshun
Abstract : Lipid coated ZnO nanoparticles (LZnO NPs) were developed as a novel lymphatic drug delivery system. High lymphotropism and tumour cells selective toxicity ensure the nanoparticles being a promising candidate for treatment of tumor metastasis. Abstract : Lymphatic metastasis plays an important role in tumour recurrence. The applications of nanoparticles in the treatment of lymphatic metastatic tumours have been limited by targeting inefficiency and nonselective toxicity. Hence, in this report, we have developed lipid-coated ZnO nanoparticles (LZnO NPs) in an attempt to solve these issues. Using the microreactor method, we have fabricated ultrasmall (∼30 nm) core–shell-structured nanoparticles loaded with 6-mercaptopurine (6-MP). In vivo results show that the lipid shell induces a remarkable improvement in lymphotropism and biocompatibility compared to ZnO nanoparticles. Furthermore, the ZnO core exhibits not only pH-responsive behaviour to guarantee effective drug delivery, but also a strong preferential ability to kill cancerous cells, as a consequence of the generation of higher inducible levels of reactive oxygen species in rapidly dividing cells. Furthermore, LZnO NPs enhance the cytotoxicity of 6-MP, resulting from the improved internalization of nanoparticles through endocytosis. These findings indicate that LZnO NPs are a promising candidate for use as lymphatic-targeted drug carriers.